The Study of Magneto-Active Polymer Composite Physiochemical Characteristics Using Petroleum Based Oil as a Dispersing Aid - Mohamad Noor, Wan Aizat (IRC, 2020)
Rubber is a natural polymer of Isoprene which has elastic properties and it undergoes long range reversible extension. Magnetorheological fluids are known to be used in shock absorbers, dampers as well as isolators. Researchers have also studied the potential of these fluids to be used in various industries. However, the limitation that they faced was due to the substance being formed in a fluid state. It is believed that by forming a solid polymer composite, numerous applications can benefit from the characteristics that it may possess. Rubber is a natural polymer of Isoprene which has elastic properties and it undergoes long range reversible extension. Rubber is also known as an elastomer that inhibits the ability of being magnetised. This is made possible by combining the polymer elastomers with magnetisable elements such as carbonyl iron particulates. In this report, we studied the physicochemical characteristics of magnetorheological elastomers which consists of rubber and carbonyl iron particulates using different types of petroleum based oil as a dispersing aid. In this case, we are using natural rubber (NR) as a matrix as well as carbonyl iron particles as the magnetisable element that would allow the presence of magnetorheological effect.